A collaborative approach to preparing for and reacting to emerald ash borer: a case study from Colorado. (23rd December 2019) - Alexander, Kathleen; Truslove, Micaela; Davis, Rob; Stephens, Sky; Zentz, Ralph
Abstract: Collaboration has been the key to success for urban forest management in Colorado, not only collaboration amongst agencies at all levels of government but also in engaging industry allies, coordinating education and outreach efforts and in fostering community support. A unique interagency team, the Emerging Pests in Colorado (EPIC) Workgroup, was formed in 2009 to address the immediate threat from Thousand Cankers Disease (TCD) of walnut and to plan for the arrival of other invasive urban forest pests to Colorado. When the emerald ash borer ( Agrilus planipennis Fairmaire) (EAB) was detected in Boulder, Colorado in 2013, it marked the westernmost occurrence of EAB in the US, threatening millions of planted and naturalized ash trees representing over 25 percent of the tree canopy throughout Colorado's urban and riparian forests. The detection in Boulder prompted the development of a second multi-agency group, the Colorado EAB Response Team (CORT). The preparedness and established working relationships between stakeholders and responsible authorities allowed for a quick, decisive and unified response. We review as a case study: (1) the formation and history of collaborative interagency groups in Colorado; (2) how the interagency collaborative planning and post-detection EAB response have supported community forestry programmes throughout the state; (3) development of the post-detection EAB management plan and economics behind the strategy in Boulder, Colorado; and (4) the proactive EAB planning and outreach efforts underway in Denver, Colorado.